Impact of aerobic, resistance, and combined training on cardiometabolic health-related indicators in inactive middle-aged men with excess body weight and obesity - Mengistu, Friew Amare; Lake, Yehualaw Alemu; Andualem, Molalign Enchalew; Miherete, Yalemsew Demlie; Zewdie, Solomon Adamu (Frontiers in Physiology, 2025)
MethodsTwenty physically inactive men (49.15 ± 2.581 years) and BMI with 27.66 ± 0.91, participated in an 8-month training programme involving concurrent exercise (CT), resistance training (RT), and aerobic training (AT) program to determine the effects on fasting blood glucose (FBG), insulin resistance (IR), blood pressure (BP) and waist–to–hip ratio (WHR) in overweight and obese adult persons. This study was used a randomized repeated measures parallel experimental design.ResultsPre-to-post mean values of FBG, IR, SBP, DBP and WHR significantly decreased. Exercise modality had a significant effect on FBG (F (2, 26) = 10.656, p = 0.001, η2 = 0.571), with RT and CT showing greater reductions than AT. IR decreased more in RT than in AT (MD = 0.410 ± 0.101, p = 0.03). SBP also varied significantly between modalities (F (2, 26) = 13.103, p = 0.02, η2 = 0.528), with CT and RT showing larger reductions than AT. WHR differed significantly (F (2, 16) = 18.175, p = 0.001, η2 = 0.694), with AT and CT showing more reductions than RT. Diastolic blood pressure (DBP) showed no significant effect from exercise modality.ConclusionThese findings highlight the importance of tailored exercise interventions, with short rest RT and CT emerging as the most effective method for inactive overweight and obese individuals.